Hubungan Tingkat Pengetahuan Orang Tua Terhadap Perilaku Penggunaan Antibiotik pada Balita ISPA di Wilayah Kerja Puskesmas Buntok: The Correlation Between Parent’s Knowledge Level and Antibiotic Use in Ari Patients in Buntok Health Center Area - Shopa Handayani; Darini Kurniawati; M. Zulfadhilah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: The problem of ARI has tended to increase in recent decades, both globally and nationally. The high prevalence of ARI and its impact has resulted in the high consumption of antibiotics. The lack of knowledge on antibiotics tends to lead to inappropriate use of antibiotics. Objective: to analyze the correlation between the level of parental knowledge and the use of antibiotics in children with ARI in the Buntok Health Center area. Methods: Research in the Buntok Community Health Center in August 2020. The type of research was analytic survey with cross sectional approach. Population and sample were parents of children under five diagnosed with ARI and receiving antibiotic therapy at Buntok Health Center. The sample part of the population was 30 people with accidental sampling technique. The instrument was a questionnaire using the google form method. Data analysis using spearman rank. Results: Most of the parents of children under five with ARI had less knowledge about antibiotics as many as 17 people (56.6%) and most of the use of antibiotics was in the moderate category, namely 23 people (76.7%). There is a relationship between parental knowledge and the use of antibiotics in children with ARI in the working area of ​​Buntok Health Center (p value = 0.000). Conclusion: Puskesmas Buntok can improve health education, for example by distributing leaflets about ARIs and the use of ARI antibiotics.